Murdoch mysteries. Once upon a Murdoch Christmas [videorecording (DVD)] - Bisson, Yannick, 1969-; Joy, Hélène; Craig, Tom, 1962-; Jennings, Maureen (Acorn Media, 2017)
Days before Christmas in turn-of-the-century Toronto, Detective William Murdoch is called to investigate a daring train robbery. When witnesses insist the culprit exhibited super-human abilities, Constable Crabtree realizes the robber bears a striking resemblance to the title character of his new graphic novel, Jumping Jack.